The Mitford trial - Fellowes, Jessica (Fellowes, Jessica. Mitford murders mystery., 2021)
"A timeless murder mystery with the fascinating, glamorous Mitford sisters at its heart, The Mitford Trial is the fourth installment in the Mitford Murders series from Jessica Fellowes, inspired by a real-life murder in a story full of intrigue, affairs and betrayal.."--